Does the Baltic Dry Index predict economic activity in South Africa? A review from 1985 to 2016 - Sartorius, K; Sartorius, B; Zuccollo, D (AOSIS, 2018)
Background: The ability of the Baltic Dry Index to predict economic activity has been evaluated in a number of developed and developing countries.